Effects of the dietary fibre inulin and Trichuris suis products on inflammatory responses in lipopolysaccharide-stimulated macrophages. (May 2020) - Myhill, Laura J.; Jensen, Penille; Zakeri, Amin; Nielsen, Lars F.; Jakobsen, Simon R.; Mejer, Helena; Thamsborg, Stig M.; Nejsum, Peter; Williams, Andrew R.
Highlights: RAW 264.7 macrophage activity is modulated by Trichuris suis soluble products. Inulin has mixed but limited direct effect on RAW 264.7 macrophage gene expression. Epithelial cells do not mediate immunomodulatory effects of inulin in vitro . Sodium butyrate reduces inflammatory cytokine secretion from RAW 264.7 macrophages. Abstract: Consumption of fermentable dietary fibres, such as inulin, or administration of helminth products ( e.g. Trichuris suis ova) have independently been shown to alleviate inflammation in vivo . We recently found that dietary inulin and T. suis infection in pigs co-operatively suppressed type-1 inflammatory responses in the gut, suggesting the potential of dietary components to augment anti-inflammatory responses induced by certain helminths. Here, we explored whether T. suis antigens and inulin could directly suppress inflammatory responses in vitro in a cooperative manner. T. suis soluble products (TsSP) strongly suppressed lipopolysaccharide (LPS)-induced IL-6 and TNF-α secretion from murine macrophages and induced an anti-inflammatory phenotype as evidenced by transcriptomic and gene pathway analyses. Inulin regulated the expression of a small number of genes and transcriptional pathways in macrophages after exposure to LPS, but did not enhance the suppressive activity of TsSP, either directly or in co-culture experiments with intestinal epithelial cells. Culture of macrophages with short-chain fatty acids, the products of microbial fermentation of inulin, did however appear to enhance TsSP-mediated inhibition of TNF-α production. Our results confirm a direct role for helminth products in suppressing inflammatory responses in macrophages. In contrast, inulin had little capacity to directly modulate LPS-induced responses. Our results suggest distinct mode-of-actions of T. suis and inulin in regulating inflammatory responses, and that the role of inulin in modulating the response to helminth infection may be dependent on other factors such as production of metabolites by the gut microbiota.